Political power and magic - Frazer, E (Routledge, 2018)
This paper considers how magic power – as a political resource, and as a metaphor for political power – is implicated in current and past thought about sovereignty and domination. Shakespeare’s treatments of politics, magic, sovereignty and domination are an illuminating source, relating as they do to the Machiavellian tradition, and to later treatments of the themes by Hobbes and Weber. The question is raised how articulated scepticism about political power relates to scepticism about alleged magic; and how the conduct of Shakespeare’s magicians casts light on their conduct qua political actors.